Solvent‐Assisted Mechanochemical Synthesis of a Nucleotide Dimer. Issue 4 (21st April 2022) - Johnston, Christopher; Migaud, Marie E.
Abstract: This article contains a synthetic protocol for solvent‐assisted mechanochemical synthesis of a nucleotide dimer. First, a dinucleoside phosphite is prepared by solvent‐assisted mechanochemistry via the phosphoramidite method. Second, the dinucleoside phosphite is oxidized to form the dinucleotide under mechanochemical conditions. Finally, the dinucleotide is purified by column chromatography. Support protocols are also provided for preparing the acidic salts that can be utilized for phosphoramidite couplings and for demonstrating that the reaction occurs under mechanochemical conditions rather than as a result of solvent added for analysis. Mechanochemistry as applied to synthesis of dinucleotides is a recent development and it is anticipated that the principles in this protocol will be widely applicable to a range of nucleoside and ribonucleoside monomers. The advantages of mechanochemistry over traditional solution‐phase chemistry are the simplicity of the procedure, improved hydrolytic stability, and elimination of the need to solubilize poorly soluble compounds. © 2022 Wiley Periodicals LLC. Basic Protocol : Solvent‐assisted mechanochemical synthesis of a nucleotide dimer Supplementary Protocol 1 : Synthesis of N ‐methylimidazolium triflate Supplementary Protocol 2 : Synthesis of pyridinium trifluoroacetate Supplementary Protocol 3 : Confirmation of the efficacy of mechanochemical conditions